2003
DOI: 10.2174/1389450033491109
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and Parenchymal Mechanisms in Multiple Drug Resistance: a Lesson from Human Epilepsy

Abstract: Long term treatment with antiepileptic drugs (AEDs) is the standard therapeutic approach to eradicate seizures. However, a small but significant number of patients fail AED treatment. Intrinsic drug resistance may depend on two main and not necessarily mutually exclusive mechanisms: 1) Loss of pharmacological target (e.g., GABAA receptors); 2) poor penetration of the drug into the central nervous system (CNS). The latter is due to the action of multiple drug resistance proteins capable of active CNS extrusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 23 publications
2
63
0
1
Order By: Relevance
“…These observations suggest that astrocytic glia in certain neural locations may be able to create diffusion barriers around critical local microenvironments. In pathologies where the mammalian brain endothelium is compromised (e.g., in tumors, epilepsy) (Bronger et al, 2005;Marroni et al, 2003), and in the glial scar around areas of damage, compensatory changes are observed in the glia, further revealing their barrier and regulatory potential (Abbott et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that astrocytic glia in certain neural locations may be able to create diffusion barriers around critical local microenvironments. In pathologies where the mammalian brain endothelium is compromised (e.g., in tumors, epilepsy) (Bronger et al, 2005;Marroni et al, 2003), and in the glial scar around areas of damage, compensatory changes are observed in the glia, further revealing their barrier and regulatory potential (Abbott et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The barrier helps establish a specialized microenvironment for optimal neuronal function (Abbott, 1992). Many neuropathologies involve BBB dysfunction, and in some cases (tumors, epilepsy), compensatory changes in the glial cells are observed, so they act as a ''second line of defense'' (Abbott et al, 2006;Bronger et al, 2005;Marroni et al, 2003). This study of the evolution of the vertebrate BBB gives insights into the origin of the division of labor between endothelial cells and astrocytes in the mammalian BBB, and helps to explain not only features of the embryonic development and adult organization of the mammalian brain, but also changes occurring in human pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Mrps are export pumps that use ATP to facilitate the efflux of organic cations (235). Regarding astrocyte expression, Mrp1 protein has been reported in rodent and human astrocytes (226,236); Mrp2 at the mRNA and protein level is lacking in astrocytes (237); Mrp3-5 have been reported at both the mRNA level and protein levels in various astrocyte preparations (237,238). Evidence in the literature supports a role of Mrp1 in AD; however, this is not conclusive.…”
Section: Atp-binding Cassette Transporter Familymentioning
confidence: 99%
“…The challenge will be to apply the knowledge gained in vitro to testing hypotheses in more intact preparations, to gain a more complete picture of normal physiology. In parallel, we should be applying information from in vitro preparations mimicking pathology (e.g., ischemia, inflammation) to understanding the real in vivo pathology (Male, 1992;De Vries et al, 1997;Marroni et al, 2003). These challenges will certainly occupy us for at least the next three decades.…”
Section: Completing the Circle: From In Vitro To In Vivomentioning
confidence: 99%